Population, ecology and conservation of Bornean elephants in Sabah, Malaysia - Raymond Alfred @ Jenry (2014)
Today, the loss of habitat has been one of the major causes of the decline in the Asian elephant population in Asia. In order to develop a conservation strategy for the Bornean elephant, it is important to know the ecology, habitat need and status of the elephant population size in the forest in Sabah. This study is the first ever effort to study the overall population and ecology of Bornean Elephants in Sabah. Five adult female elephants were immobilized and their neck collars were fitted with tracking devices. The sizes of their home range and movement patterns were determined using location data gathered from a satellite tracking system and were analyzed by using the Minimum Convex Polygon and Harmonic Mean methods. The home range size for a period of one year in a non-fragmented forest was estimated to be 150 km2 to 200 km2 and in a fragmented forest was 256 km2 . The ranging behavior for the elephants was influenced by the size of the natural forest habitat and the availability of permanent water sources. 140 food plants species taken by elephants were recorded through direct observation. Five main food plants for Bornean elephants includes (i) Palmae, (ii) Moraceae, (iii) Euphorbiaceae, (iv) Leguminoceae, and (v) Graminaeae. Out of 140 plants and trees species consumed by the elephant, at least 35% is affected by silviculture activities while 14.3% of the trees are categorized as a commercial tree. Therefore, at least 49.3 % from 140 plants and trees species could be affected by the forestry activities such as harvesting and silviculture activities. it is suggested that the Borneon elephants in the rainforests are classified as both, browsers and grazers. The diversity of food plants is lower in primary forest and poor forest (treeless habitat), and is higher in forest less degraded and moderate forest. Although Sabah still has a continuous forest landscape in the central part of the state, not all of the area is suitable elephant habitat. This study provides a systematic approach for identification of key habitat for large mammals in a large area. The survey indicates that approximately 2,040 (95% Cl: 1,184-3,652) elephants remain in the five main ranges in Sabah, with the largest population being in the unprotected central forests. Elephant density was highest in ranges where habitat has been removed and elephants are concentrated in remaining forest areas. These ecological and population data provide new baseline data to support the implementation of Bornean elephant conservation programme in Sabah.